Walking and health care expenditures among adult users of the Brazilian public healthcare system: retrospective cross-sectional study - Turi, Bruna Camilo [UNESP]; Codogno, Jamile Sanches [UNESP]; Fernandes, Romulo Araujo [UNESP]; Monteiro, Henrique Luiz [UNESP] (Abrasco, 2015)
Physical inactivity is a major public health challenge due to its association with chronic diseases and the resulting economic impact on the public healthcare system. However, walking can help alleviate these problems. Aim: To verify associations between walking during leisure-time, risk factors and health care expenditure among users of the Brazilian public health care system. Methods: The sample consisted of 963 adults. Walking was evaluated using the Baecke questionnaire. The total expenditure per year was evaluated through the demand for health care services, verified in the medical records of each participant. Results: Walking was reported as a physical activity during leisure-time by 64.4% of the participants. The group with the highest engagement in walking was younger and presented lower values for BMI, WC and expenditure on medication. Participants inserted in the category of higher involvement in walking were 41% less likely to be inserted into the group with higher total expenditure (OR = 0:59; 95% CI 0.39-0.89). Conclusion: It was found that walking was the most frequent leisure-time physical activity reported by users of the Brazilian health care system and was associated with lower total and medication expenditure.
Keywords: Walking; Health care expenditure; Primary health care